Pengaruh Suntik 3 Bulan Terhadap Peningkatan Berat Badan di Balai Penyuluhan KB Desa Parpaudangan Tahun 2023 - Theresia Rina Novia Sinaga; Rumondang Sitorus; Eva Dona Sinaga (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The still high population growth is one of the polemics that occurs in Indonesia, so that Indonesia is still called a developing country. Therefore, the government's effort to suppress population growth is by establishing the Family Planning Family Planning program. The aim of this research is to analyze the effect of 3-month birth control injections on increasing body weight at the Family Planning Extension Center in Parpaudangan Village, North Labuhan Batu in 2023. This research is quantitative with a case control research design carried out at the Parpaudangan Family Planning Extension Center. The population in this study was 35 mothers who came to visit the family planning extension center. The sampling technique used was purposive sampling. In this research, the instruments used were primary data and secondary data as well as bivariate analysis using the Chi Square test with a confidence level of 95%. In conclusion, the statistical test results show an OR (Odds Ratio) of 2.310 with calculated X2 (2.089) < X2 Table (3.841) or p (0.148) > α (0.050) and CI (0.872; 6.118). The results of this research show that 3-month contraceptive injections are not a significant factor as the main cause of weight gain, but acceptors of 3-month contraceptive injections are likely to experience weight gain 2 times greater than non-acceptors of 3-month contraceptives, at the Parpaudangan village family planning extension center in 2023 .